Facilitating collaborative professional development among instrumental and vocal teachers: A qualitative study with an Austrian Music School - Kruse-Weber, Silke; Bucura, Elizabeth; Tumler, Margareth (Frontiers in Psychology, 2023)
This case study provides an in-depth investigation in a professional development project about facilitating collaborative reflection. This was led by a research team from the university with 13 instrumental music teachers from one music school in Styria (Austria) during 2019–2021 (including the initial COVID-19 pandemic). Research questions considered (1) the participants’ descriptions of the collaborative professional development, (2) participants’ uses of reflection tools and indications of their identification with workshop interventions, as well as factors responsible for the outcomes from the reflection tools; and (3) ways participants’ thinking and attitudes may have developed through the workshops, how they defined themselves as a group (if they did), and how they might have gained trust in one another. Inspired by the design-based research approach, practitioners and researchers worked closely together to enhance teaching and learning implementing interventions with collaborative reflections tools. While the first phase (11 workshops) was primarily led by the project-team, the second phase (7 workshops) was participant-led. Data included focus groups and discussion transcriptions from 18 workshops. The impetus of the study included the role of the director and the participants dealing with the interventions, and finally the participants’ descriptions of their experiences in the professionalization process. Literature included collaborative professional development, community of practice, learning communities, self-determined learning, reflective practice, and ethical considerations. Data were analyzed based on thematic analysis and gave rise to five following themes: forming group cohesion, inspiring and appreciating collaboration, bridging theory and practice, identifying deeper thinking and teachers as learners, addressing challenges and potentials during the COVID-19 pandemic, and finally finding the music school’s own identity and sense of importance. Findings highlight the importance of establishing meaningful collaborative reflection through appreciative communication and an atmosphere of trust and respect. To be able to make change in and with an institution, leadership members must be engaged as collaborative stakeholders on an eye-level; collaborative professional development can be used as a resource toward rethinking and reworking the identity of one’s music school and of teaching and learning. Institutions should provide space and continuity for such development. Finally, the study highlights that a collaborative reflective approach can contribute to professional and social growth.